Faktor - Faktor yang Mempengaruhi Kepatuhan Minum Obat Anti - Hipertensi pada Pasien di Wilayah Kerja Puskesmas Baiturrahman Banda Aceh - Elysia Katri; Wardiati Wardiati; Dharina Baharuddin (Yayasan Literasi Sains Indonesia, 2026)
Hypertension is a major contributing factor to premature death globally, with an incidence rate of 30.8% in Indonesia. In Banda Aceh, the Baiturrahman Community Health Center recorded the highest number of cases, with 895 cases in 2024. This study aims to analyze various factors influencing patient adherence to antihypertensive medication. The research method used a quantitative approach with a cross-sectional design with 98 respondents. Data were collected through structured interviews from June 16 to 26, 2025. Data processing was carried out sequentially, starting with univariate analysis, followed by bivariate analysis using the chi-square test, and then multivariate analysis through multiple logistic regression with a stepwise approach using Stata/MP 17 software. This study has received ethical approval from the Health Research Ethics Committee of the Aceh Ministry of Health Polytechnic (No: DP.04.03/12.7/266/2025). The results showed that 45.92% of respondents were compliant with taking medication, while 54.08% were non-compliant. Multivariate analysis showed significant predictors of adherence, namely gender (p = 0.040; OR = 3.53), the role of health workers (p = 0.037; OR = 3.13), access to health services (p = 0.036; OR = 3.36), health literacy (p = 0.014; OR = 10.14), and family support (p = 0.002; OR = 7.97). The model has a Pseudo R² value of 0.36 indicating that the model is able to explain approximately 36% of the existing differences. The conclusion of the study shows that adherence to antihypertensive medication is significantly influenced by gender, the role of health workers, access to services, health literacy, and family support.